2010
DOI: 10.2166/wh.2010.090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection, quantification and characterization of human polyomavirus JC from waste water in Rio De Janeiro, Brazil

Abstract: Polyomavirus JC (JCPyV) is largely excreted by the human population through the urinary route and has been recognized as a potential viral marker for human waste contamination. This study aims to investigate the dissemination of JCPyV in waste water from a sewage treatment plant (STP) located in Rio de Janeiro, Brazil, and to describe the prevalence of JCPyV subtypes currently present in this population. Raw and treated sewage samples were collected bimonthly during one year, and examined for the presence of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 31 publications
5
23
1
2
Order By: Relevance
“…In this study, the percentages of raw and treated sewage samples testing positive for the enteroviruses genome using both concentration methods were 100 %. These results are in concordance with other studies raising concerns about viral contamination risk in treated water [15,26,27]. Enteroviral genomes concentration in raw and treated sewage were high in comparison with studies made on Human adenoviruses and polyomaviruses ranging between 10 2 and 10 3 (GC/mL), respectively, in sewage samples [15,28].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the percentages of raw and treated sewage samples testing positive for the enteroviruses genome using both concentration methods were 100 %. These results are in concordance with other studies raising concerns about viral contamination risk in treated water [15,26,27]. Enteroviral genomes concentration in raw and treated sewage were high in comparison with studies made on Human adenoviruses and polyomaviruses ranging between 10 2 and 10 3 (GC/mL), respectively, in sewage samples [15,28].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported that adenovirus and polyomavirus are predominant in the environment [19][20][21]. Examples of some viral indicator candidates include phages of Bacteroides fragilis and coliphages (e.g., F-RNA phages) [22][23][24][25].…”
Section: Traditional Pathogen Detection Techniques (Culture-based Metmentioning
confidence: 99%
“…Examples of some viral indicator candidates include phages of Bacteroides fragilis and coliphages (e.g., F-RNA phages) [22][23][24][25]. In addition, adenovirus, polyomavirus, norovirus, and enterovirus have been recognized as potential viral markers for human waste contamination [21,[26][27][28]. Hepatitis A and E viruses are associated with poor countries that lack sanitation and strict hygiene controls.…”
Section: Traditional Pathogen Detection Techniques (Culture-based Metmentioning
confidence: 99%
“…Several studies (Mucillo et al 2008;Miagostovich et al 2008;Lee et al 2013) point out that the AdVs can be considered a reliable indicator of fecal pollution for environmental monitoring. Although other viruses, such as JC polyomavirus (JCPyV), coliphage, and bacteriophages, have been proposed as potential viral contamination indicators in different environmental matrices (Albinana-Gimenez et al 2009;Fumian et al 2010), the AdVs have advantages over other markers, since they are stable, easily detected in the environment, and can be isolated in several cell culture for assessing viral viability AlbinanaGimenez et al 2009;Schlindwein et al 2010 …”
Section: Statistical Analysis Of Various Environmental Parametersmentioning
confidence: 99%